Evaluate the effectiveness of hydrotherapy versus land-based exercises outcome on pain and quality of life among patients with rheumatoid arthritis: triple-blind randomized controlled trial - Jinjwaria, Rajendra Kumar (International Journal of Clinical Trials, 2023)
Background: Evaluate the effectiveness of hydrotherapy versus land-based exercise outcomes to decrease pain and improve the quality of life among patients with rheumatoid arthritis. Methods: Triple-blind, randomized controlled, parallel-group, multiple arm trial was conducted between 29/09/2019 to 30/09/2021 at the Department of PMR, KG University Lucknow India and randomization was done through the SNSOE. Eligible 90 patients suffering from rheumatoid arthritis. The intervention (RJHLERA) was administered in both study groups. NRPS used for pain and RJQOL-22 Scale was used for QoL. Results: The pre-test results showed all the subject’s average pain scores and quality of life had either poor or neither poor nor good levels of the RJQOL-22 scale. At the post-test, in terms of pain, the hydrotherapy exercise group showed the maximum response with an average pain score of 3.64±1.89, the land-based exercises group showed the next to maximum response with an average pain score of 5.88±1.37 while the control group showed the least response with an average pain score of 7.63±1.41. and in terms of quality of life, the hydrotherapy exercise group showed the maximum response with 67.9% very good, and 21.4% good. The land-based exercises group showed the next to maximum response with 19.2% good while the group the clear control group showed the least response. Conclusions: Effectiveness of hydrotherapy versus land-based exercises, in comparison to land-based exercises the Hydrotherapy exercises group showed the maximum response to reduce the pain and improve the quality of life among chronic rheumatoid arthritis patients.